Optimization of the Bioenergy Supply Chain Under Governmental Intervention Policies - Yuqiang Wu; Weiwei Guo; Jingpeng Chen; Jianru Shang; Zigong Cai; Shuangliang Luo (IEEE Access)
Amidst global efforts to reduce carbon emissions, the significance of bioenergy as a sustainable alternative has become increasingly prominent. To promote the development of the bioenergy industry, corresponding intervention policies are indispensable. This paper explores the role of government intervention policies—the Skill Training Policy (STP) and the Promotion Relationship Policy (PRP)—in advancing the bioenergy sector within a contract farming framework. This paper develops models to analyze the optimal government intervention policies by capturing the strategic interactions between the government, the bioenergy company, and the farmer. The findings reveal that both STP and PRP increase biomass feedstocks supply and the profit for the farmer and the bioenergy company, enhancing overall social welfare. Specially, When the implementation cost of STP is low enough, it can enable the farmer and the bioenergy company to achieve higher profits and assist the government in achieving greater social welfare than PRP. When the green benefit from bioenergy is high, STP can more effectively promote the supply of biomass feedstocks and enhance social welfare. However, when the green benefit is relatively low, PRP is a better choice. This research provides insights for policymakers to tailor government subsidies to promote the bioenergy industry efficiently.